Learning Arabic language in China: Investigation on instrumental and integrative motivations of Chinese Arabic learners - Al-Nahdi, Yousef Ali Ahmed; Zhao, Shuo (Technium Social Sciences Journal, 2022)
There is an increasing demand in recent years for the study of the Arabic language by foreign learners as a second language, especially Chinese students. There are wide ranges of necessity to Arabic languages, such as commercial, industrial, economic, cultural, political, media, and other fields. Many foreign learners are learning this language to increase demands in all areas of life and use it in non-Arabic-speaking countries. China is one of those earliest countries that took this advantage and offered this program for an academic major. It’s almost 37 universities and institutes where the Arabic language is taught in China. The request for learning this language has increased because of the urgent need for exchange programs with Arab-speaking countries. As result, international experts believe motivations are an important factor in teaching Arabic to non-speakers that can be influential reasons for the foreign learners to practice, argue, push and motivate them to benefit more and overcome the difficulties of the Arabic language. This study examines two facial types of motivations, instrumental and integrative motivations. In this study, all participants are Chinese students currently studying in China. The number of participants was 125 students from both genders, including 4 academic directors of the Arabic language department in five public Chinese Universities. The findings show that Chinese students learning Arabic as a Second Language (ASL) are highly instrumental than integrative to studying Arabic. A lack of experience of the Arabic language in their classrooms and society guides their attitude. The findings also revealed that there is a relationship between the language structure and a classroom environment that decreases their motivation and achievements of learning Arabic.